The integration of logic model in business plan simulation approach for effective entrepreneurial learning - Mohd Guzairy Abd Ghani; Norhidayah Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2021)
Entrepreneurship education plays a vital role in entrepreneurship development. Risk-taking, creative problem-solving, social involvement, and role-playing should all be part of entrepreneurial learning. The logic model was used to evaluate business simulation. Efficacy and self-control can be improved in real-life situations by students. This research aims to find the integration of the logic model that contributes to effective entrepreneurial learning. We conducted a sample of 272 students taking a business plan simulation as part of entrepreneurial learning. PLS structural equation modelling was used to evaluate the logic model. The study found that there was a significant relationship between the input (student characteristics, lecturer characteristics, and simulation content) and the output (learning effectiveness), with the process of as a mediator (experiential learning). However, this research was limited to a selected university and students of an entrepreneurship course. The business plan simulation is also limited to offline use, which is based on VBA Excel. The research highlights the need for business simulations as an exercise and training for future business planning. Experiential learning is a factor that facilitates learning in a simulated environment. This study’s findings also have practical consequences for future entrepreneurs and managers.